Implementasi Next.Js, Typescript, Dan Tailwind Css Untuk Pengembangan Aplikasi Frontend Sistem Inventory Perusahaan Apar (Studi Kasus: CV Indoka Surya Jaya) - Arya Bayu Wirya Kesuma, Ketut; Wijaya, I Nyoman Yudi Anggara; Putra, I Gede Juliana Eka (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
This research succeeded in developing an internal management system using Next.js for the integration of key features such as customer, supplier, category, unit, product, purchase and invoice management. The use of TypeScript increases code security and clarity, and ensures the system is verified through Black Box Testing. Implementing Tailwind CSS in creating company landing pages strengthens online representation with a responsive and modern design. It is hoped that this system can significantly increase operational efficiency and be adaptive to changes in company needs in the future.